Personal Interest and Persistence among Female Engineering Doctoral Students at an International Islamic University in Malaysia - Abd Karim, Aishah Hanim; Kangani, Kokab (IIUM Journal of Educational Studies, 2026)
Although women’s participation in STEM has expanded, doctoral persistence remains influenced by complex psychological and contextual factors. In Malaysia, existing research largely emphasizes undergraduate retention, with limited qualitative attention to women’s persistence at the PhD level. This study explores the role of personal interest in shaping persistence among female engineering doctoral students at the International Islamic University Malaysia (IIUM). Guided by Social Cognitive Career Theory (SCCT), a qualitative approach was employed using semi-structured interviews with nine female lecturers in multiple engineering disciplines. Data were analyzed through thematic analysis. Findings indicate that personal interest operates as a dynamic and developmental mechanism across four dimensions: early formation through exposure and encouragement; identity-integrated interest shaped by belonging and academic success; value-integrated interest linked to societal contribution; and sustained passion functioning as motivational energy. Interest evolved from early academic socialization into a deeply internalized commitment that reinforced persistence throughout prolonged doctoral challenges. The findings extend SCCT by conceptualizing interest as an evolving psychological process central to doctoral completion in STEM within a Malaysian higher education context.